Mycotoxin Uptake in Wheat — Eavesdropping Fusarium Presence for Priming Plant Defenses or a Trojan Horse to Weaken Them? - Righetti, Laura; Bhandari, Dhaka Ram; Rolli, Enrico; Tortorella, Sara; Bruni, Renato; Dall’Asta, Chiara; Spengler, Bernhard (Frontiers in Plant Science, 2021)
Fusarium mycotoxins represent a major threat for cereal crops and food safety. While previous investigations have described plant biotransforming properties on mycotoxins or metabolic relapses of fungal infections in plants, so far, the potential consequences of radical exposure in healthy crops are mostly unknown. Therefore, we aimed at evaluating whether the exposure to mycotoxins, deoxynivalenol (DON) and zearalenone (ZEN), at the plant-soil interface may be considered a form of biotic stress capable of inducing priming or a potential initiation of fungal attack. To address this, we used atmospheric-pressure scanning microprobe matrix-assisted laser desorption/ionization mass spectrometry imaging to investigate the activation or the inhibition of specific biosynthetic pathways and in situ localization of primary and secondary metabolites in wheat. According to our untargeted metabolomics investigation, the translocation of plant defense metabolites (i.e., hydroxycinnamic acid amide and flavones) follows the mycotoxin accumulation organs, which is the root for ZEN-treated plantlet and culm for DON-treated sample, suggesting a local “defense-on-demand response.” Therefore, it can be hypothesized that DON and ZEN are involved in the eavesdropping of Fusarium presence in soil and that wheat response based on secondary metabolites may operate on multiple organs with a potential interplay that involves masked mycotoxins.